A Moving Experience - Honorton, Charles (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> <p class="MSGENFONTSTYLENAMETEMPLATEROLENUMBERMSGENFONTSTYLENAMEBYROLETEXT30" style="margin-top: 0in; margin-right: 1.0pt; margin-bottom: 22.45pt; margin-left: 1.0pt; text-align: left; background: transparent;" align="left">ABSTRACT: This is a popular account of the author's firsthand observations of special subject Felicia Parise's experimental work at the Maimonides Dream Laboratory and her ability to move small objects apparently by PK. It was originally written as a chapter of a book on parapsychology that was never published. Parise's macro-PK, which is featured in the article, was inspired by firsthand observations of Soviet star PK subject Nina Kulagina made by Western parapsychologists Montague Ullman, Gaither Pratt, and Jiirgen Keil. Honorton describes Parise's first solo efforts, his own observations, and those of a magician/photographer, Norman Moses, who made a film of her moving objects. Also described is research conducted by Gaither Pratt at the University of Virginia and by Graham and Anita Watkins at the Institute for Parapsychology in Durham, NC. Parise specialized in moving pill bottles and compass needles, and in film fogging. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>